Blood Type Profile in Relation to the Prevalence of Metabolic Diseases and Diabetes Mellitus at Kraton Regional General Hospital, Pekalongan Regency - Wibowo, Subur; Safanah, Asti (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Diabetes mellitus is one of the chronic metabolic diseases whose prevalence continues to increase in Indonesia and is the third leading cause of death in the country. The main disorder in diabetes is carbohydrate metabolism, which causes chronic hyperglycemia and poses a risk of complications in various organs of the body, such as the eyes, kidneys, nerves, heart, and blood vessels. In addition to genetic factors and lifestyle, several studies have shown an association between ABO blood type and the tendency to develop type 2 diabetes mellitus. This study aims to determine the distribution of blood types in relation to the tendency for metabolic diabetes mellitus at Kraton District General Hospital in Pekalongan. Method: This study used a descriptive design with 35 samples collected through total sampling among diabetes mellitus patients at Kraton District General Hospital in Pekalongan. Blood type testing was conducted using the slide method. Result: The results showed that blood type B had the highest percentage (40%), followed by blood type A (28.57%), blood type O (20%), and blood type AB (11.43%). Conclusion: It can be concluded that blood type B has a high percentage (40%) compared to other blood types. This indicates that blood type B is more dominant among diabetes mellitus patients in the sample at Kraton District General Hospital, Pekalongan.